Grain spotting of rice caused by Pestalotiopsis guepinii (Desm.) Stay – A new record (Dhaka University Journal of Biological Sciences, 2015)
Abstract not availableDhaka Univ. J. Biol. Sci. 24(1): 103-106, 2015 (January)